The Absence of Calponin 2 in Rabbits Suggests Caution in Choosing Animal Models - Plazyo, Olesya; Hao, Weilong; Jin, Jian-Ping (Frontiers in Bioengineering and Biotechnology, 2020)
While the rapid development of CRISPR/CAS9 technology has made it feasible to readily produce site-specific genomic editing in non-rodent species, an emerging challenge is to select the most suitable species to generate models of human biology and diseases. Improving CRISPR/CAS9 methodology for more effective and precise editing in the rabbit genome to replicate human disease is an active area of biological research. Although rabbit is more closely related to human than mouse to human based on DNA sequence analysis, our whole-genome protein database search revealed that rabbit lacks 2146 human protein sequences, approximately 30% more than the number of missing human protein sequences in mouse. Hence, precisely replicating human diseases in rabbit requires further consideration, especially in studies involving essential functions of the missing proteins. As shown in the example reported here, rabbit lacks calponin 2, an actin-associated cytoskeletal protein with well-documented cell motility functions and roles in the pathogenesis of arthritis, atherosclerosis, and calcific aortic valve disease. Although rabbit is larger in size and is considered phylogenetically closer to humans based on the sequence similarity of the conserved genes, this approach to justify its use as a model for human biology and diseases may be misleading whereas the whole-genome protein profiling appears to be more informative. Our findings serve as a warning to the scientific community to consider the overall conservation as well as conservation of specific proteins when choosing an animal model to study a particular aspect of human biology prior to investing effort into genetic engineering.